10z-z=-1+2z-2-18

Simple and best practice solution for 10z-z=-1+2z-2-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10z-z=-1+2z-2-18 equation:


Simplifying
10z + -1z = -1 + 2z + -2 + -18

Combine like terms: 10z + -1z = 9z
9z = -1 + 2z + -2 + -18

Reorder the terms:
9z = -1 + -2 + -18 + 2z

Combine like terms: -1 + -2 = -3
9z = -3 + -18 + 2z

Combine like terms: -3 + -18 = -21
9z = -21 + 2z

Solving
9z = -21 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
9z + -2z = -21 + 2z + -2z

Combine like terms: 9z + -2z = 7z
7z = -21 + 2z + -2z

Combine like terms: 2z + -2z = 0
7z = -21 + 0
7z = -21

Divide each side by '7'.
z = -3

Simplifying
z = -3

See similar equations:

| x^2+4x-3=3x-1 | | 22=6v+2(v+3) | | 5m+n=0 | | 5v-2(1-3v)=-68 | | 4x^2-25x+41=2x+6 | | -66=-6(x+6) | | P+e=f | | x^2+5x-34=2 | | 8k=6k-28 | | 6u+5(u-8)=-7 | | x^2+5x+34=2 | | -118=6-4(5k+6) | | x^2+5x-34=0 | | 3(x+5)+2x=10 | | -130=5(-6+4x) | | x^2+23x+38=9x-2 | | -6(4k+4)+4=124 | | 4p+21=9 | | 5g-2=20 | | 4x^2+20x+15=0 | | 2.4h=3.6 | | 6-x=4(10+30) | | x^2+x-27=3 | | -4r=20 | | 212-3x=255 | | -5(x+1)+3(3x-6)=3(x-4)+13 | | 7u=20 | | 3j+5k=19 | | 12x+27=4x+163 | | (x-3)(2x-5)=(x-3)(4x+7) | | .59=3x-.91 | | 66-3x=24x+18 |

Equations solver categories